Coders at Work - Seibel, Peter (Apress, 2012)
Leaving aside the work of Ada Lovelace—the 19th century countess who devised algorithms for Charles Babbage’s never-completed Analytical Engine—computer programming has existed as a human endeavor for less than one human lifetime: it has been only 68 years since Konrad Zuse unveiled his Z3 electro-mechanical computer in 1941, the first working general-purpose computer. And it’s been only 64 years since six women— Kay Antonelli, Jean Bartik, Betty Holberton, Marlyn Meltzer, Frances Spence, and Ruth Teitelbaum—were pulled from the ranks of the U.S. Army’s “computer corps”, the women who computed ballistics tables by hand, to become the first programmers of ENIAC, the first general-purpose electronic computer. There are many people alive today—the leading edge of the Baby Boom generation and all of the Boomers’ parents—who were born into a world without computer programmers.